Measuring counterproductive work behavior in telework settings: Development and validation of the Counterproductive [Tele]work Behavior Scale (CTwBS) - Junça Silva, A.; Martins, S. (International Journal of Organizational Analysis, 2025)
Purpose Although (tele)work is increasingly being adopted and employees’ behavior is recognized to be key for organizational outcomes (e.g. performance), the current literature on counterproductive work behaviors (CWB) in telework settings is fragmented, and a valid measurement instrument is lacking. This study aims to address this gap and starts by presenting a review of the current literature on counterproductive work behavior in flexible work arrangements (i.e. telework). Based on this study, eight categories of work behavior that appear to be frequent under telework settings were identified. Design/Methodology Next, four studies aimed at developing and validating a measurement instrument that captures employee counterproductive work behavior when teleworking: the counterproductive [tele]work behavior scale (CTwBS). Findings In Study 1, the CTwBS was created, and in Study 2, its factorial validity was examined (N = 350). In Study 3, using a sample of teleworkers (N = 289), the convergent and discriminant validity of the CTwBS was tested using self-ratings of (positive and negative) affect, attitudes toward telework and frequency of CWB in general. In Study 4, a daily-diary study across five workdays (N = 232 × 5 = 1,160) examined the criterion validity of the CTwBS. Practical implications The results indicated that the CTwBS is a valid and reliable instrument for capturing employee counterproductive work behavior in telework settings. Theoretical and practical implications are discussed. Originality To the best of the authors’ knowledge, CTwBS is the first measure aimed at assessing counterproductive work behavior in telework settings.